Long‐term potentiation in neurogliaform interneurons modulates excitation–inhibition balance in the temporoammonic pathway - Mercier, Marion S.; Magloire, Vincent; Cornford, Jonathan H.; Kullmann, Dimitri M. (The Journal of physiology, 2022)
Apical dendrites of pyramidal neurons integrate information from higher‐order cortex and thalamus, and gate signalling and plasticity at proximal synapses. In the hippocampus, neurogliaform cells and other interneurons located within stratum lacunosum‐moleculare (SLM) mediate powerful inhibition of CA1 pyramidal neuron distal dendrites. Is the recruitment of such inhibition itself subject to use‐dependent plasticity, and if so, what induction rules apply? Here we show that interneurons in mouse SLM exhibit Hebbian NMDA receptor‐dependent long‐term potentiation (LTP). Such plasticity can be induced by selective optogenetic stimulation of afferents in the temporoammonic pathway from the entorhinal cortex (EC), but not by equivalent stimulation of afferents from the thalamic nucleus reuniens. We further show that theta‐burst patterns of afferent firing induces LTP in neurogliaform interneurons identified using neuron‐derived neurotrophic factor (Ndnf)‐Cre mice. Theta‐burst activity of EC afferents led to an increase in disynaptic feed‐forward inhibition, but not monosynaptic excitation, of CA1 pyramidal neurons. Activity‐dependent synaptic plasticity in SLM interneurons thus alters the excitation–inhibition balance at EC inputs to the apical dendrites of pyramidal neurons, implying a dynamic role for these interneurons in gating CA1 dendritic computations. Key points Electrogenic phenomena in distal dendrites of principal neurons in the hippocampus have a major role in gating synaptic plasticity at afferent synapses on proximal dendrites. Apical dendrites also receive powerful feed‐forward inhibition, mediated in large part by neurogliaform neurons. Here we show that theta‐burst activity in afferents from the entorhinal cortex (EC) induces ‘Hebbian’ long‐term potentiation (LTP) at excitatory synapses recruiting these GABAergic cells. LTP in interneurons innervating apical dendrites increases disynaptic inhibition of principal neurons, thus shifting the excitation–inhibition balance in the temporoammonic (TA) pathway in favour of inhibition, with implications for computations and learning rules in proximal dendrites. figure legend Hebbian long‐term potentiation (LTP) of excitatory transmission onto interneurons located within hippocampal stratum lacunosum‐moleculare (SLM) can be induced by electrical stimulation protocols involving pairing of pre‐ and postsynaptic activity. Using Ndnf‐Cre mice, we show that hippocampal neurogliaform (NGF) cells express this form of LTP. These cells receive glutamatergic afferents from both the nucleus reuniens of the thalamus and the entorhinal cortex (EC), but selective optogenetic activation of either set of fibres reveals LTP at EC inputs only. Using an optogenetic theta‐burst stimulation (OptoTBS) protocol to stimulate EC fibres in a physiologically relevant way, we show that NGF interneuron LTP translates to an increase in disynaptic inhibition onto CA1 pyramidal cell distal dendrites. Monosynaptic EC–CA1 pyramidal cell inputs do not undergo equivalent potentiation, leading to a net decrease in the excitation/inhibition (E/I) ratio of this pathway.